2019
DOI: 10.1590/s0004-2803.201900000-78
|View full text |Cite
|
Sign up to set email alerts
|

Altered Esophageal Motility During Perception of Bolus Transit in Healthy Volunteers

Abstract: BACKGROUND: The perception of bolus transit through the thoracic esophagus may be caused by altered esophageal anatomy and function. OBJECTIVE: To evaluate the hypothesis that, in healthy volunteers, swallows followed by perception of esophageal bolus transit are associated with changes in esophageal motility. METHODS: Simultaneous evaluation of motility and perception of esophageal bolus transit was performed in 22 healthy volunteers. Esophageal motility was evaluated by high-resolution manometry with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Besides, healthy individuals with the perception of esophageal bolus transit may have physiological alterations at this level. A recent study conducted on healthy participants by Costa et al concluded that the perception of bolus transit was associated with changes in proximal esophageal motility [ 7 ]. Yet, it remains unknown whether these changes are related to the transitioning of muscle types or related to the sensitivity of receptors in proximal esophageal mucosa which activate and mediate peristalsis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, healthy individuals with the perception of esophageal bolus transit may have physiological alterations at this level. A recent study conducted on healthy participants by Costa et al concluded that the perception of bolus transit was associated with changes in proximal esophageal motility [ 7 ]. Yet, it remains unknown whether these changes are related to the transitioning of muscle types or related to the sensitivity of receptors in proximal esophageal mucosa which activate and mediate peristalsis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%